The Impact of the Fourth Industrial Revolution on Southern African Higher Education - Vurayai, Simon (International Journal of Knowledge Content Development & Technology, 2025)
This study examined the impact of the fourth industrial revolution (4IR) on higher education in Southern Africa. Results from the study suggest that the impact of 4IR on higher education can be encapsulated by its potentials in revolutionizing the way knowledge is produced, accessed, and disseminated through innovative pedagogical approaches and cutting-edge research activities, and the way higher education institutions are governed and operated, commonly known as the digitalization of higher education. The study recommended that policy makers need to actively advocate for the provision of resources and development programmes to support technological capacity among academics and students within the Southern African higher education sector.